Chronic Kidney Disease in community-dwelling adults aged 50+ years in Ireland: A Report from TILDA and the National Renal Office - O'Halloran, Aisling; Mellotte, George; Sexton, Donal; Kenny, Rose (My University, 2023)
The presence and severity of CKD identifies individuals who are at increased risk of adverse health outcomes and premature mortality; and as such, preventing and managing CKD constitutes a key aim of overall management. We conducted the largest longitudinal study performed in Ireland using data from TILDA to describe the clinical epidemiology of CKD in Ireland. Based on data from 2009-2011 to 2013-2015, CKD prevalence in adults aged 50 years and over in Ireland is rising . While this is likely to be primarily related to ageing and improved survival in the general population, these trends highlight the importance of continued public health action to raise awareness and to improve the care and outcomes for people with CKD. -→ Based on data from Wave 3 of TILDA (2013-2015) integrated with the last Irish Census estimates, the national prevalence of CKD Stage ≥ 3 is 15.6%, with increasing prevalence with age and in female sex. The estimated national prevalence was 4.9% and 35.8% in people aged 50-69 years and 70+ years, respectively, which translated to 50,496 adults aged 50-69, and 152,882 adults aged 70+ living with CKD in Ireland in 2016. The new eGFR formula (2022), which removes the race adjustment from the regression equation, yielded similar albeit slightly lower estimates of CKD prevalence/incidence. Hypertension was the most common CKD-related condition in the Irish adult population. The estimated prevalence of CKD in Irish adults aged 50+ years without diabetes and hypertension was 6.22 % based on Wave 1 data and 10.01% based on Wave 3 of TILDA. Age, blood pressure, HbA1c, BMI and hypertension were significantly associated with the presence and severity of CKD. Based on eGFR grading, 15.6% of the Irish population aged 50+ years have CKD and are at increased risk of adverse outcomes related to CKD including cardiovascular disease, premature mortality and the development of End Stage Kidney Disease (ESKD). More than 5% of the Irish population aged 50+ years have more advanced CKD by eGFR grading and are even more at risk of these adverse outcomes. Our study supports the previously observed association between ageing, impaired kidney function and kidney function decline over follow up. The incidence of CKD ≥ stage 3 was 16 per 1000 person-years which will likely contribute to substantial future demand on Nephrology services .
PUBLISHED
Keywords: Ageing